Synthesis of Nitrogen doped TiO2 with superior ultrafast charging properties - Tang, Ernest Jun Jie (Nanyang Technological University, 2019)
Rechargeable Lithium Ion Batteries (LIB) have garnered numerous interests in the last few decades due to various advantages over traditional lead-acid batteries. In addition, with the gaining traction of usage of renewable energies and transition to technology dependent era, batteries provide the required source of portable electrical power. However, currently lithium ion batteries have various limitations such as commonly used graphite anode has low intercalation voltage with respect to Li/Li+, which results in safety hazards due to lithium dendrite formation. As such new materials are developed to address this issue. One material of focus would be the use of Titanium Dioxide nanotubes, bronze phase, known as TiO2 as an anode material for LIB applications. The higher intercalation voltage of approximately 1.5 V with respect to Li/Li+ makes it a viable and safe alternative anode material. Through nano-structuring, titanate nanotubes are synthesised with TiO2 phase for this experiment due to its high theoretical specific capacity of 335 mAh/g among titanate polymorphs and the electrochemical benefits of nanotube structure. Given that pure titanate has a relatively poor electron conductivity, doping of the TiO2 nanotubes with nitrogen through calcination with urea is done to improve the electrochemical performance of the N-TiO2 nanotubes to achieve higher specific capacity for both low and high charge and discharge rates as compared to existing pure TiO2 nanotubes. As such, these TiO2 nanotubes will have pseudocapacitive properties which could be viable for ultra-fast charging applications. This has proven to be successful and the as-synthesised N-TiO2 nanotubes have an improvement in specific capacity of at least 85% at discharge-charge rates of 10 C and above. In addition, the N-TiO2 anode have shown superior cyclability with a specific capacity of approximately 130 mAh/g and near 100% capacity retention even after 500 cycles. As such, this shows a proof of concept of the superior ultra-fast charging properties